A New Rule : The Swiss Debt Brake - Danninger, Stephan (Washington, D.C. : International Monetary Fund, 2002)
The paper provides an international comparison and a comprehensive analysis of a new fiscal expenditure rule for the federal government in Switzerland. The proposed rule has two innovative features: it aims at a structurally balanced budget in the short-run by annually setting a cyclically adjusted expenditure ceiling, and it arrests the accumulation of public debt via corrections of future expenditure targets for past deviations from projected fiscal balances. The paper finds that the new rule is likely to reduce procyclical tendencies in fiscal policy and that its objectives are adequate in meeting long-run fiscal challenges arising from demographic changes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet